2010
DOI: 10.1098/rstb.2010.0145
|View full text |Cite
|
Sign up to set email alerts
|

Toward a synthetic understanding of the role of phenology in ecology and evolution

Abstract: Phenology affects nearly all aspects of ecology and evolution. Virtually all biological phenomenafrom individual physiology to interspecific relationships to global nutrient fluxes-have annual cycles and are influenced by the timing of abiotic events. Recent years have seen a surge of interest in this topic, as an increasing number of studies document phenological responses to climate change. Much recent research has addressed the genetic controls on phenology, modelling techniques and ecosystem-level and evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
537
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 597 publications
(553 citation statements)
references
References 169 publications
(201 reference statements)
5
537
2
9
Order By: Relevance
“…phenotypic plasticity | snow downscaling | rhythm | phenological mismatch | threshold trait S hifts in annual timing of life history events are a common response of plant and animal populations to climate change (1,2). In many cases, these phenological shifts span multiple trophic levels, creating mistiming as animal reproduction (3), hibernation emergence (4,5), or migration (6) become detached from peak timing of food or habitat structure (7).…”
mentioning
confidence: 99%
“…phenotypic plasticity | snow downscaling | rhythm | phenological mismatch | threshold trait S hifts in annual timing of life history events are a common response of plant and animal populations to climate change (1,2). In many cases, these phenological shifts span multiple trophic levels, creating mistiming as animal reproduction (3), hibernation emergence (4,5), or migration (6) become detached from peak timing of food or habitat structure (7).…”
mentioning
confidence: 99%
“…In this review, we have summarized the diversity and complexity of the mechanisms that underlie phenology. The control and expression of annual cycles vary in the degree of flexibility depending on the species, on the environment where they live and on the temporal cues that affect their physiological systems [4,5]. The difficulties in explaining organismic responses may be largely owing to our limited understanding of the diverse timing mechanisms, and specifically to a neglect of contributions by biological clocks.…”
Section: (B) Urbanizationmentioning
confidence: 99%
“…Phenology, the seasonal timing of recurring biological processes, is the result of these complex, and species-specific, timing processes [3,4]. Because of the particularly evident importance of understanding seasonal timing in the context of global warming, phenology is an increasingly active field of study [4,5]. Organisms have different mechanisms underlying annual cycles, but generally combine internal time-keeping with information from external cues to prepare for predictable, annual changes in their environment.…”
Section: Mechanisms Of Annual Timingmentioning
confidence: 99%
“…For instance, studying cowpox virus in voles, Begon et al [24] found that susceptible recruitment is seasonal, and higher breeding-season birth rates delayed epidemic peaks. However, despite evidence demonstrating the importance of host demography in recurrent epidemics [25][26][27][28], and the ubiquitous appreciation of seasonal reproduction in broader ecology and evolution [29], we submit that a deep understanding of the dynamical impact of birth seasonality on infectious diseases of humans is currently lacking.…”
Section: Introductionmentioning
confidence: 99%